Diagnosis of sacroiliitis: characteristics of anatomical variants of the sacroiliac joint structure and their significance for clinical practice - Sh. F. Erdes; T. V. Dubinina (Научно-практическая ревматология, 2025)
Inflammation of the sacroiliac joints (SIJ) – sacroiliitis (SI) – is an obligatory criterion of axial spondyloarthritis. The main place in the diagnosis of SI is occupied by X-rays and magnetic resonance imaging (MRI). Anatomical features of the SIJ structure can mimic the signs of radiologic and active SI according to MRI, which often leads to diagnostic errors. The article discusses the variability of anatomical changes of the SIJ and its correlation with imaging findings.